COPD and cognitive impairment: a review of associated factors and intervention strategies - Jing, Yuling; Mao, Shuixiang (Frontiers in Psychiatry, 2026)
Chronic obstructive pulmonary disease (COPD) is increasingly recognized as a systemic disorder associated with heightened risk of cognitive impairment, including mild cognitive impairment (MCI) and dementia. Epidemiological studies indicate COPD patients face a 1.74-fold higher risk of cognitive decline, with deficits predominantly affecting attention, memory, and executive functions, impairing daily living and increasing mortality risk. This review synthesizes factors linking COPD to cognitive impairment, including systemic inflammation (via proinflammatory cytokines and blood-brain barrier disruption), hypoxemia/hypercapnia (inducing oxidative stress and neuronal damage), acute exacerbations (exacerbating inflammation and persisting deficits), and comorbidities like obstructive sleep apnoea (OSA), cerebral microbleeds, and depression. Smoking’s role remains paradoxical, with neurotoxicants potentially counteracted by nicotine’s neuroprotective effects. Assessment relies on neuropsychological tools (e.g., MoCA, MMSE), neurophysiological measures (P300 ERP), and neuroimaging, though limitations persist. Interventions focus on non-pharmacological strategies: pulmonary rehabilitation (improving cognition via enhanced cerebral perfusion), cognitive training (targeting memory/attention), and long-term oxygen therapy (LTOT, reducing decline in hypoxemic patients). Critical gaps include unclear mechanisms and the need for personalized interventions. Addressing these may improve clinical outcomes and quality of life in COPD patients.